2015
DOI: 10.14303/irjm.2015.139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes on occurrence of urinary tract infection and asymptomatic bacteriuria among diabetic and ketacidosis patients in Egypt

Abstract: Diabetic patients have a higher risk of infections which is the leading trigger of diabetic ketoacidosis. The second most common infection in diabetics is urinary tract infection (UTI). Elevation of glucose level induces an inflammatory process within numerous tissues in the body leading to disturbance in cytokines level and oxidative stress. This study is divided into two parts, firstly it was to investigate the prevalence of asymptomatic bacteriuria (ASB) and urinary tract infections in 84 Type 1 diabetes pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In a similar study, the mean duration of diabetes and mean HBA1c levels were significantly higher in ASB positive as compared with ASB-negative patients. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, the mean duration of diabetes and mean HBA1c levels were significantly higher in ASB positive as compared with ASB-negative patients. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is going on with other studies done in Egypt and showed also high prevalence of UTI among diabetic patients. [14], [19] Patients with diabetes have a 10-fold increased risk of UTI when compared to non-diabetics in a previous study [20]. Prevalence of UTIs infection and asymptomatic bacteriuria in diabetic patients ranges from 11% to 68 % in some of international studies [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has found that 64.2% of T1DM patients had positive urine culture with bacteriuria and pyuria, and 77.7% of T2DM patients had positive urine culture and pyuria. The study revealed that Escherichia coli was the most common isolated uropathogen [19].…”
Section: Discussionmentioning
confidence: 99%